KINERJA METODE CEPAT UNTUK EVALUASI KEBERSIHAN PERALATAN PRODUKSI PANGAN - Vanessa Len Cahya Agustine; Siti Nurjanah; Ratih Dewanti Hariyadi (AGROINTEK, 2021)
Sanitation programs for equipment in food production are designed to reduce the number of microorganisms. Food industries verify the fullfilment of sanitation programs using various methods. This study aimed to evaluate the performance of several methods for evaluate of cleanliness of food production equipment. Escherichia coli, Klebsiella and protein residues that were artificially contaminated on stainless steel plates and the number of bacteria and or protein were analyzed using microbiological method with chromogenic media EB, ATP method with bioluminesence assay and protein method with semiquantitative method. The sensitivity and correlation of each method was measured using statistical data. The results showed that the chromogenic media EB and ATP bioluminesence were able to detect the contamination of Escherichia coli and Klebsiella at the lowest concentration of 1 log CFU. The result using chromogenic media EB showed correlation values were 0.9846 and 0.9946, while ATP method showed the correlation value is 0.9785 and 0.9681. ATP and protein method are able to detect protein at high concentrations, but ATP method is positively correlated to the amount of protein residue with a correlation value is 0.884. Concluded that the chromogenic media EB, ATP and protein method able to detect contamination on equipment with fullfilment the performance evaluation.